2017
DOI: 10.1055/s-0042-120324
|View full text |Cite
|
Sign up to set email alerts
|

Velocity Loss as a Variable for Monitoring Resistance Exercise

Abstract: This study aimed to analyze: 1) the pattern of repetition velocity decline during a single set to failure against different submaximal loads (50-85% 1RM) in the bench press exercise; and 2) the reliability of the percentage of performed repetitions, with respect to the maximum possible number that can be completed, when different magnitudes of velocity loss have been reached within each set. Twenty-two men performed 8 tests of maximum number of repetitions (MNR) against loads of 50-55-60-65-70-75-80-85% 1RM, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
200
8
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(234 citation statements)
references
References 31 publications
21
200
8
5
Order By: Relevance
“…This demonstrates varying rates of barbell velocity loss during exercise (e.g. a rapid loss in velocity versus a gradual decline) and supports previous research that has demonstrated athletes may need to perform a varying number of repetitions prior to achieving a given percentage of velocity loss 25 . This could be explained by training history and/or differing levels of muscular endurance 4 .…”
Section: Discussionsupporting
confidence: 85%
“…This demonstrates varying rates of barbell velocity loss during exercise (e.g. a rapid loss in velocity versus a gradual decline) and supports previous research that has demonstrated athletes may need to perform a varying number of repetitions prior to achieving a given percentage of velocity loss 25 . This could be explained by training history and/or differing levels of muscular endurance 4 .…”
Section: Discussionsupporting
confidence: 85%
“…It has been widely argued in the scientist literature that training to muscular failure (i.e., performing the maximum number of repetitions possible with a given relative load) is unnecessary and probably detrimental to maximizing athletic performance [3,4]. Velocity loss (VL) has been recently proposed as a precise and non-invasive variable to monitor the actual degree or level of effort incurred during resistance training [5], a very high relationship having been found between the relative velocity loss in a training set and the percentage of performed repetitions with respect to the maximum possible number that can be completed in the bench press and pull-up exercises [6,7]. For this reason, training methods that reduce the amount of induced fatigue and allow maintenance of maximum velocity in every repetition during resistance training have been shown to optimize strength and performance gains [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The submaximal load of 10 RM (repetition maximum) estimated percentage 80% of 1RM [24] will be individually calculated based on momentary muscle failure (inability to perform 10 concentric contractions without significant posture change and repetition velocity during changes against a 8 certain resistance) [25]. To calculate the submaximal load of 10 RM, weight will be added until momentary muscle failure of the individual is achieved during calf raise exercises.…”
Section: Resistance Trainingmentioning
confidence: 99%